DRUG THERAPY AND FLU PREVENTION - V.К. Tatochenko (Педиатрическая фармакология)
The article discusses the treatment and prevention of influenza. Data on application of the basic drugs used during treatment (interferon, neuraminidase inhibitors rimantadine and DR.) and the rates of their effectiveness are presented. Tactics of fever relief is described in details. Key words: influenza, treatment, prevention, children.